1984
DOI: 10.1136/bmj.288.6418.693
|View full text |Cite
|
Sign up to set email alerts
|

Total and free thyroid hormone concentrations in patients receiving maintenance replacement treatment with thyroxine.

Abstract: Total and free serum concentrations of thyroxine and triiodothyronine were measured in 122 subjects with hypothyroidism who were clinically well while receiving conventional replacement treatment with thyroxine. In a third of patients concentrations of total and free thyroxine were raised, often considerably; nevertheless concentrations of total and free triiodothyronine were usually normal. Though significant correlations were obtained between total triiodothyronine concentrations and total thyroxine concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 11 publications
(1 reference statement)
2
33
0
1
Order By: Relevance
“…Several studies regarding the use of L-T 4 therapy to treat hypothyroidism showed that when serum T 4 levels are maintained at the upper limit of the normal ranges, serum T 3 levels are within the normal ranges (4,5,6,7,8). However, there have been few studies that compared postoperative T 3 levels in patients on L-T 4 therapy with their own preoperative endogenous levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies regarding the use of L-T 4 therapy to treat hypothyroidism showed that when serum T 4 levels are maintained at the upper limit of the normal ranges, serum T 3 levels are within the normal ranges (4,5,6,7,8). However, there have been few studies that compared postoperative T 3 levels in patients on L-T 4 therapy with their own preoperative endogenous levels.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of TSH, FT 4 , and FT 3 were measured by a chemiluminescent immunoassay (ARCHTECT i2000; Abbott Japan). TSH assay showed an intra-assay coefficient of variation (CV) of 1.1-5.0% and an interassay CV of 1.7-5.3%.…”
Section: Thyroid Function Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the integration in CMOS, the here developed biosensor principle has a high potential for applications in the 10 pM to 0.1 M range, e.g. for the observation of thyroid functionality [14]. …”
Section: Resultsmentioning
confidence: 99%
“…According to Woeber K.A., a higher ratio of T4 to T3 is due to the suppression of the residual T3 secretion by the thyroid gland and low conversion of T4 to T3 in the peripheral tissues on the exogenous L-T4 therapy. It has been demonstrated in earlier studies, that replacement therapy of hypothyroidism with L-T4 is accompanied by increased ratio of T4 to T3 in the blood [Pearce CJ, 1984, Rendell M., 1985, Stock JM, 1974, and this ratio grows up with increasing doses of L-T4.…”
Section: Levels Of Thyroid Hormones On the Replacement Monotherapy Wimentioning
confidence: 99%